PENGARUH TIMES INTEREST EARNED RATIO DAN NET PROFIT MARGIN TERHADAP RETURN ON EQUITY DI GUDANG GARAM TBK PERIODE 2015-2020 - Mira Purnamasari (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This research aims to identify and analyze how the influence of Times Interest Earned Ratio (TIER) and Net Profit Margin (NPM) to Return On Equity (ROE). Research uses quantitative with statistical procedures. The data used is secondary data in the the form of data on Gudang Garam Tbk financial statements obtained from the source of the Indonesia stock exchange (IDX) for period 2015-2020. The variable used are Times Interest Earned Ratio (X1), Net Profit Margin (X2) and Return On Equity (Y). The data analysis techniques used are normality tests. Classical assumption tests, multiple linier regression tests and hypothesis tests. The results of the analysis obtained that simultaneously Times Interest Earned Ratio (TIER) and Net Profit Margin (NPM) affect Return On Equity (ROE). Partially, the Times Interest Earned Ratio (TIER) has no effect on Return On Equity (ROE), while Net Profit Margin (NPM) affects Return On Equity (ROE). Keywords: Times Interest Earned Ratio, Net Profit Margin, Return on Equity.